Indonesia's Strategy to Build Geopolitical Identity as a Middle Maritime Power in the Indo-Pacific Through the World Maritime Axis (PMD) Policy in the Era of the Joko Widodo Administration (2014-2019) - Rikko Yan Lado Ae; Roberto Octavianus Cornelis Seba; Indra Wisnu Wibisono (Journal of Law, Politic and Humanities, 2026)
This study analyzes Indonesia's strategy in building a geopolitical identity as a middle maritime power in the Indo-Pacific region through the Global Maritime Fulcrum (GMF) policy during the Joko Widodo administration (2014–2019). The background of this study is based on the increasing geopolitical dynamics of the Indo-Pacific as the epicenter of great power rivalry, which demands Indonesia to strengthen its strategic position and identity as an archipelagic nation. This study uses a descriptive qualitative approach based on literature studies with reference to Middle Power Theory as a theoretical framework, as well as the concepts of maritime geopolitics, the Indo-Pacific, and maritime diplomacy as conceptual frameworks. The study shows that the GAM does not only function as a maritime sector development policy, but also as a grand strategy in shaping Indonesia's identity as a middle maritime power.